2000
DOI: 10.1177/095646240001100207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Drama-in-Education Programme to Increase AIDS Awareness in South African High Schools: A Randomized Community Intervention Trial

Abstract: A community intervention trial was undertaken in KwaZulu Natal, South Africa to evaluate the effectiveness of a high school drama-in-education programme. Seven pairs of secondary schools were randomized to receive either written information about HIV/AIDS or the drama programme. Questionnaire surveys of knowledge, attitude and behaviour were compared before and 6 months after the interventions. One thousand and eighty students participated in the first survey and 699 in the second. Improvements in knowledge (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 11 publications
1
63
0
Order By: Relevance
“…Use of media such as videos and audio tapes was also common. Two studies relied on drama, including creating plays and skits, for the bulk of the intervention [61], [62] and one study used a comic book to impart information [63]. Two studies were internet-based [36], [64] and involved students completing online modules during school hours at their own pace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of media such as videos and audio tapes was also common. Two studies relied on drama, including creating plays and skits, for the bulk of the intervention [61], [62] and one study used a comic book to impart information [63]. Two studies were internet-based [36], [64] and involved students completing online modules during school hours at their own pace.…”
Section: Resultsmentioning
confidence: 99%
“…The measures used to assess HIV-related knowledge varied by study but centered on aspects such as HIV biology, HIV transmission, and HIV prevention. Some studies measuring HIV-related knowledge were excluded from meta-analysis for not controlling for baseline differences in socio-demographics or outcome variables (n = 3) [29], [71], [72], not providing enough data to convert results into standardized effect sizes (n = 18) [36], [47]–[50], [56], [57], [62], [63], [65], [69], [73][78], presenting knowledge outcomes not specifically related to HIV (n = 2), such as asking students whether they knew about HIV/AIDS [58], and measuring how many STIs students correctly identified [66].…”
Section: Resultsmentioning
confidence: 99%
“…A longitudinal study conducted in schools in South Africa revealed significant improvements in HIV-related knowledge and attitudes gained through drama-in-education compared with written curricula, an effect that lasted for the entire study duration of six months. 10 This finding suggests that the observed improvement in knowledge and attitudes based on exposure to the drama performances in Haiti could be sustained over longer periods. This hypothesis warrants further research.…”
Section: Discussionmentioning
confidence: 93%
“…Long-term retention studies can only be performed in settings with regular attendance, such as schools, where a longitudinal design is feasible. 10,11,12 However, school studies limit participants to students, excluding older people and those who cannot afford to attend school. In addition, many religiously-administered schools, which provide a large proportion of the education in Haiti and in other developing countries, may not be amenable to certain interventions, such as instruction regarding condom use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation